2019
DOI: 10.1088/2058-8585/ab0cea
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing and characterisation of a resistive temperature sensor on paper substrate

Abstract: Resistive temperature sensors on two different commercially available uncoated paper substrates have been manufactured using inkjet printing of silver nanoparticles. Their dedication is to be integrated in lightweight materials made from natural fibre-reinforced biopolymers for condition monitoring during the manufacturing process and beyond. The printed sensors have nominal resistances of a few hundred Ohms and kOhms, depending on the roughness and porosity of the respective paper substrate. Compared to previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…Therefore, it needs to be considered that for most printed sensors, e.g., for resistive sensing applications [30][31][32][33], it is crucial to design structures with a predefined total resistance that guarantee some degree of reproducibility, as otherwise each sensor would have to be calibrated individually. However, inkjet-printed conductive layers on porous substrates (e.g., paper) have no homogeneous surface, as well as a varying thickness of a few micrometres, which is little related to its planar dimensions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it needs to be considered that for most printed sensors, e.g., for resistive sensing applications [30][31][32][33], it is crucial to design structures with a predefined total resistance that guarantee some degree of reproducibility, as otherwise each sensor would have to be calibrated individually. However, inkjet-printed conductive layers on porous substrates (e.g., paper) have no homogeneous surface, as well as a varying thickness of a few micrometres, which is little related to its planar dimensions [34].…”
Section: Introductionmentioning
confidence: 99%
“…Further, whereas our data were obtained using stylus profilometry, those of Barras and Johansson arise from 2D optical system, strongly indicating that the linear dependence of R q on R a is not an artefact of the measurement system. For completeness, we note also that the data of Zikulnig et al [6] obtained using white light interferometry on two commercial papers give the ratio of R q -R a as approximately 1.35. Figure 6 shows R q plotted against R a for the data of El-kharouf et al [8] obtained using interferometry of nonwoven carbon fibre networks used in gas diffusion layers in fuel cells.…”
Section: Resultsmentioning
confidence: 71%
“…Morais et al [5] investigated the use of papers with different roughnesses as substrates for organic electronic devices and observed a strong dependence of sheet resistance on surface roughness. Similarly, Zikulnig et al [6] observed an order of magnitude difference in the resistance of printed silver nanoparticle sensors on paper substrates, which was attributed to differences in surface roughness and sheet porosity. Further, Liu et al [7] noted the influence of roughness not only on the global electrical performance of carbon nanotube thin-film transistors on paper, but on its local uniformity also.…”
Section: Introductionmentioning
confidence: 89%
“…Courbat et al [ 40 ] inkjet-printed lines of Ag NP-based ink on paper for the realization of both humidity and temperature sensors with a TCR of 0.0011 °C −1 ; also, it has been exhibited that overcoating with parylene did not influence temperature sensing properties. Similarly, Zikulnig et al [ 57 ] printed and evaluated an Ag meander geometry on different types of paper; Kapton has also been proven to be an effective substrate for Ag-based temperature sensors; Dankoco et al [ 58 ] inkjet-printed an organic silver complex compound ink. The corresponding results include a TCR of 2.19 × 10 –3 °C −1 in the range of 20–60 °C ( Figure 16 e).…”
Section: Printed Temperature Sensorsmentioning
confidence: 99%